Comparison of Cd bioavailability determination methods and the risk control value of Cd for typical Cd-contaminated paddy soils in Guangdong - LI Jihong (Agro-Environmental Protection Institute, Ministry of Agriculture, 2021)
This study aimed to find a suitable method for determining the bioavailability and risk control value of cadmium(Cd) in typical Cd-contaminated paddy soils in Guangdong to provide technical support for the safe use of these paddy fields. Four available Cd extraction methods(CaCl2, HCl, EDTA, and DTPA) were used and systematically compared for three typical Cd-contaminated paddy soil samples collected from Shaoguan (SG), Qingyuan (QY), and Guangzhou (NC) in Guangdong. Correlation analyses were performed on the Cd accumulated in the plant parts of two rice varieties and the available Cd content in soil. In addition, the risk control values of Cd were determined for each extraction method based on the food safety standard(0.2 mg ·kg-1) of Cd in brown rice. The results showed that the extraction capacities of the four chemical extractants for soil Cd were 0.1 mol·L-1 HCl > 0.05 mol·L-1 EDTA > 0.005 mol·L-1 DTPA > 0.1 mol·L-1 CaCl2. When Cd was artificially added, soil Cd availability was high. Both the total Cd content and available Cd content of soil were significantly correlated with the Cd content of brown rice(P < 0.01), and the correlation coefficients between the available Cd in soil(i.e., HCl-Cd, EDTA-Cd, DTPA-Cd, and CaCl2-Cd) and the cumulative Cd uptake by rice all exceeded 0.9, with that between CaCl2-Cd and Cd uptake by rice being the highest. However, for the naturally polluted soils, the correlation between the total Cd content of soil and the cumulative Cd uptake by rice was weaker than that between the available Cd content of soil and Cd uptake by rice. According to the correlations between the total or available Cd contents of soil and the Cd content of brown rice, method-dependent risk control values of Cd were determined for Cd-contaminated rice fields in Guangdong. Soil available Cd, HCl-Cd, EDTA-Cd, DTPA-Cd, and CaCl2-Cd provided better indicators of Cd bioavailability in the acidic paddy soils in Guangdong than the total Cd content of soil. Among HCl-Cd, EDTA-Cd, DTPA-Cd, and CaCl2-Cd, CaCl2-Cd had the strongest correlation with the Cd content of rice. Further in-depth research should be conducted on the development of pollution risk control values of Cd in paddy soils based on CaCl2-Cd.